PERFORMASI AYAT-AYAT AL-QUR’AN SEBAGAI PA’JA’PPI PADA MASYARAKAT BUGIS DUSUN 3 WATANGMELLE DESA MELLE - Junaid, Muh. Nasruddin A Junaid bin (Program Studi Ilmu Al-Qur'an dan Tafsir, Universitas Islam Negeri Datokarama Palu, 2023)
Pa'ja'ppi is one of the mantras used by almost all bugis people for the treatment of diseases, where there are two types of pa'ja'ppi, namely the local language and verses of the Qur'an. This field research aims to examine the pa'ja'ppi carried out by the people of Dusun 3 Watangmeelle, Melle Village, using verses from the Qur'an as pa'ja'ppinya. In answering and completing this goal, researchers use qualitative descriptive methods and phenomenological approaches, to explain cultural phenomena found in society. The result is pa'ja'ppi verses of the Qur'an used in Qs. Asy-Shams 91: 14 and Qs. Al-Anfal 8: 17. And in the treatment process that is carried out it varies, ranging from using a knife, a glass filled with water or using nothing, that is, simply reading the verse and then blowing it towards the patient's body.